Intellectual Women (Peel-Complete Hadith Misogynistic About The Less Sense A Woman) - Shofwan Al Jauhari (IAIN Tulungagung, 2020)
Abstract In this paper, the author tries to thoroughly analyze the misogynistic hadith which describes that woman lacks her sense of religion and reason. The method used by the author is to extract the hadiths from the main books, analyze them with quotes from figures from several disciplines that have relevance to the theme of the discussion. This method will answer the problem in a comprehensive and representative manner regarding women who lack reason and religion, so that the understanding generated from a hadith can be scientifically justified and clear, saved from misunderstanding. Keywords: Misogynist, Woman, Intellect, Hadith. Abstrak Artikel ini penulis mencoba mengupas secara tuntas tentang hadīs misoginis yang menggambarkan wanita itu kurang akal dan agamanya. Metode yang digunakan oleh penulis adalah dengan mentakhrij hadīs dari sumber kitab-kitab induk, menganalisanya dengan beberapa kutipan para tokoh dari beberapa disiplin ilmu yang mempunyai relevansi dengan tema pembahasan. Metode ini akan menjawab masalah secara komprehensif dan representatif mengenai wanita kurang akal dan agamanya, sehingga pemahaman yang dihasilkan dari sebuah hadīs bisa dipertanggung jawabkan secara ilmiah dan jelas, terselamatkan dari kesalah-fahaman. Kata Kunci : Misoginis, Wanita, Akal, Hadīs.